Kemampuan, berpikir kritis Penerapan Model Pembelajaran Problem Based Learning Berbantu Aplikasi Qr-Code Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Mata Pelajaran PPKn Kelas XI Ips 2 SMAN 2 Muaro Jambi: Model Pembelajaran Problem Based Learning, Aplikasi Qr-Code, Berpikir Kritis, PPKn - Rina; Pandapotan Simaremare, Tohap (Civic Education Perspective Journal, 2024)
The purpose of this study was to determine whether the Problem Based Learning learning model in collaboration with the Qr-Code application media can help students adapt to technology and can improve knowledge or add activities in the learning process of class XI Ips 2 students of SMAN 2 Muaro Jambi in the 2021/2022 academic year. This study uses classroom action research that actively involves teachers in data collection and data analysis. There are three cycles planned for this study with each cycle having three meetings or a total of nine meetings. There are four steps in implementing this classroom action research, namely: 1) planning, 2) implementation of actions, 3) observation and evaluation, 4) analysis and reflection. In collecting data in this study, student activity observation sheets and teacher activity observation sheets, documentation and tests were used. The results of the study showed that after the Action was carried out with Nine meetings or three learning cycles using the problem based learning model collaborated with the Qr-Code application at SMAN 2 Muaro Jambi, it increased the Critical Thinking Skills of class XI Ips 2 students. The results of the third cycle showed that 75% of students had met the criteria for success in critical thinking skills with the "high" category. This increased from 59% in cycle I, 69% achieved in cycle II, and 75% achieved in cycle III.